Fretting Wear Behavior and Damage Mechanisms of Inconel X-750 Alloy in Dry Contacts - Ibrohim A. Rustamov; Ozoda Sh. Sabirova; Zixi Wang; Yuming Wang (Advances in Materials Science and Engineering)
Tribological behavior of the Inconel X-750 alloy disk subjected to fretting against the GCr15 steel ball was investigated in an ambient laboratory air with relative humidity of 55–65%. A high-frequency oscillating Optimol SRV 4 tribometer was employed to execute dry fretting tests in the partial and gross slip regimes under constant 100 N normal load. Tests were carried out for 10, 30, and 90 minutes, and the friction forces vs. displacement amplitudes were monitored during the test duration. Posttest examinations were conducted utilizing advanced tools such as 3D optical surface profiler, scanning electron microscopy (SEM), and energy dispersive X-ray spectroscopy (EDX). The main objective was to obtain wear scar evolutions, frictional properties, and degradation mechanisms under the different running conditions over time. It was found that fretting wear behaviors of friction pairs were strongly influenced by fretting regimes. Degradation evolutions were greatly influenced by fretting time during partial slip regimes, i.e., evolving from asperity deformation and slight damage to the fatigue crack and material transfer. However, the combination of adhesive, abrasive, delamination, and wear oxidation mechanisms was repeated during the entire gross slip fretting process.